The Use of Tractography-Based Targeting in Deep Brain Stimulation for Psychiatric Indications - Davidson, Benjamin; Lipsman, Nir; Meng, Ying; Rabin, Jennifer S.; Giacobbe, Peter; Hamani, Clement (Frontiers in Human Neuroscience, 2020)
Deep Brain Stimulation (DBS) has been investigated as a treatment option for patients with refractory psychiatric illness. Over the past two decades, neuroimaging developments have helped to advance the field, particularly the use of diffusion tensor imaging (DTI) and tractographic reconstruction of white-matter pathways. In this article, we review translational considerations and how DTI and tractography have been used to improve targeting during DBS surgery for depression, obsessive compulsive disorder (OCD) and post-traumatic stress disorder (PTSD).